The encroachment framework 2 - van der Rhee, Bo; Schmidt, Glen (Henry Stewart Talks, 2014)
The encroachment framework, Implementing the encroachment framework, Brief history of the video games industry, Case study, Wii, Implement the framework, Position your new product or service for success